Relapse Vulnerability among Peer Counselors in Drug Rehabilitation Services - Razanah Afina Turfa; Rudi Saprudin Darwis Darwis; Hery Wibowo (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Drug relapse remain one of the major challenges in rehabilitation services, including among peer counselors who are directly involved in assisting drug users during the recovery process. This study aims to analyze interpersonal factors influencing the vulnerability to relapse among peer counselors in drug rehabilitation services. The research employed a qualitative descriptive approach conducted at Yayasan Grapiks. Data were collected through in-dept interviews, observation, and documentation involving peer counselors and supporting informants in rehabilitation services. The findings revealed that interpersonal factor significantly influence the vulnerability to relapse among peer counselors. Social support from family, colleagues, and the rehabilitation environment contributes positively to maintaining the recovery process. However, close interpersonal relationships with clients, exposure to active drug-use environment and the lack of professional supervision increase emotional pressure and vulnerability to relapse. In addition, limited institutional support causes peer counselors to face psychological burdens independently during the assistance process. Therefore, strengthening peer counselors’ capacity through psychosocial support, professional supervision, and reinforcement of professional boundaries is necessary to maintain recovery stability and improve the quality of rehabilitation service.